Impact of COVID-19 pandemic on mental and physical health of students (schools and colleges) and teachers - Kaur, Surinder; Cheema, Sangeeta; Cheema, Prerna; Kaur, Amandeep; Singla, Anju (International Journal Of Community Medicine And Public Health, 2022)
Background: Mental health issues are the leading impediment to academic success. During COVID-19 pandemic, a decrease in well-being and an increase in mental health problems were registered. Younger people and women seemed to be particularly affected by the isolation strategies, leading to development of loneliness, anxiety, depression and extreme mental stress. The objectives of the present study were to assess the core symptoms of depression, anxiety and stress in students and teachers during covid pandemic second wave. Methods: An E-Performa was created as google form. All the students and Teachers were requested to fill this Performa and submit it. The collected responses were analyzed statistically and a p<0.05 was considered to be significant. Results: A total of 483 responses were collected. Death from COVID was reported either in the family/friend’s family or neighbourhood in 122 (27.1%) students and (45.5%) teachers which was very stressful for them and it was significantly associated with negative emotions arising out of depression, anxiety and stress. Sleep pattern was reported to be disturbed in 246 (54.6%) students and 57.6% teachers. Conclusions: Everyone around the globe was distressed and scared of deadly virus. But young generation was more effected mentally and some physically also. Teachers as well as students should be prepared for such type of disastrous management. Students from underprivileged families should be rehabilitated both for physical and mental health issues.